Tracking Clinical Status for Heart Failure Patients using Ballistocardiography and Electrocardiography Signal Features - Etemadi, Mozziyar (Conf Proc IEEE Eng Med Biol Soc, 2014)
Heart failure (HF) is an escalating public health problem, with few effective methods for home monitoring. In HF management, the important clinical factors to monitor include symptoms, fluid status, cardiac output, and blood pressure – based on these factors, inotrope and diuretic dosages are adjusted day-by-day to control the disorder and improve the patient’s status towards a successful discharge. Previously, the ballistocardiogram (BCG) measured on a weighing scale has been shown to be capable of detecting changes in cardiac output and contractility for healthy subjects. In this study, we investigated whether the BCG and electrocardiogram (ECG) signals measured on a wireless modified scale could accurately track the clinical status of HF patients during their hospital stay. Using logistic regression, we found that the root-mean-square (RMS) power of the BCG provided a good fit for clinical status, as determined based on clinical measurements and symptoms, for the 85 patient days studied from 10 patients (p < 0.01). These results provide a promising foundation for future studies aimed at using the BCG / ECG scale at home to track HF patient status remotely.